The Illusion of the “Slippery Slope”: How Religion and Culture Shape Canadian Doctors’ Attitudes toward Euthanasia and Physician-Assisted Suicide - Chambers, Stuart (Université d'Ottawa | University of Ottawa, 2011)
From 1988-1995 the majority of physicians within the Canadian Medical Association supported the prohibition against an intentionally hastened death for the terminally ill. Their main concerns entailed the “slippery slope” of the Dutch medical model and a possible return to Nazi eugenics. However, empirical evidence from this time period did not support physicians’ fears of decriminalization. Therefore, it is important to understand why doctors, known for their reliance on empiricism and rational thought, reverted to uncritical and profoundly held beliefs when it came to discussions over statesanctioned euthanasia and assisted suicide. This paper suggests that two motives were pivotal in shaping Canadian doctors’ attitudes toward prohibition: the influence of religion and a lack of exposure to cross-cultural perspectives.
Keywords: euthanasia; physician-assisted suicide; “slippery slope”; Holland; Remmelink Report; Nazi eugenics; Canadian Medical Association; sanctity of life; religious attitudes; culture